Employees' Turnover Intention to Leave: The Malaysian Contexts - Kuean, Wan Li; Khin, Edward Wong Sek; Kaur, Sharon (The South East Asian Journal of Management, 2010)
This study examines the relationship between organizational commitment and employees' intention to leave the organization in the Malaysian context, and the moderating effects of participation in decision making and work effort on this relationship. It is a descriptive study based on a survey conducted among working adults in Malaysia. The results of the study suggest that all three dimension of organizational commitment; affective commitment, continuance commitment, and normative commitment; have significant association with intention to leave. Participation in decision making was found to have a significant effect on intention to leave, while the time commitment dimension of work effort was found to be not significant. Implications for practitioners and avenues for further research were discussed. This study has also provided greater understanding on the relationship between the tested variables with turnover intention. Findings of the study would assist practitioners, managers, and policy makers of organizations to formulate appropriate strateges particularly in the areas identified to be having an effect on turnover intention. The organization could pursue a commitment strategy to obtain a committed workforce through application of suitable human resource policies. Cultivating an organization culture of shared values and involving employess in the goal setting precoess would further enhance employees' acceptance of and aligment with organizational goals that would promote greater organizational commitment and eventually reduce employees' intention to leave the organization.